Procurement and Logistic Processes - Neyfe Sablón Cossío; Giselle Rodríguez-Rudi; Roberto Wilman Rosales Bonilla; Jessica Elizabeth Medina Arias; Ana Julia Acevedo-Urquiaga; Rogelio Suárez Mella (ITEGAM-JETIA)
Nowadays, managing procurement processes in companies and supply chains facilitates competitiveness among actors. In this study, the objective was to evaluate the performance of procurement processes in Ecuadorian companies. To achieve this, a modified verification instrument was used, composed of the dimensions: the importance of procurement and its relation to supply chains, procurement, suppliers, cycle, cost and human talent training. The instrument evaluated the performance of procurement areas in 162 Ecuadorian companies. The instrument was validated and the data was processed using descriptive and inferential statistics. The results of this study show a low performance level in the procurement areas in the observed companies. The weakest variables were: procurement, demand and providers. The study contributres with relevant data that can be used to create strategies to improve the procurement performance in Ecuadorian companies .